Shock-wave processing of C sub(60) in hydrogen - Biennier, L; Jayaram, V; Suas-David, N; Georges, R; Singh, M Kiran; Arunan, E; Kassi, S; Dartois, E; Reddy, K P J (Astronomy and astrophysics (Berlin), 2017)
Context. Interstellar carbonaceous particles and molecules are subject to intense shocks in astrophysical environments. Shocks induce a rapid raise in temperature and density which strongly affects the chemical and physical properties of both the gas and solid phases of the interstellar matter. Aims. The shock-induced thermal processing of C sub(60) particles in hydrogen has been investigated in the laboratory under controlled conditions up to 3900 K with the help of a material shock-tube. Methods. The solid residues generated by the exposure of a C sub(60)/H sub(2) mixture to a millisecond shock wave were collected and analyzed using X-ray diffraction, scanning electron microscopy, transmission electron microscopy, Raman micro-spectroscopy, and infrared micro-spectroscopy. The gaseous products were analyzed by Gas Chromatography and Cavity Ring Down Spectroscopy. Results. Volatile end-products appear above reflected shock gas temperatures of ~2540 K and reveal the substantial presence of small molecules with one or two C atoms. These observations confirm the role played by the C sub(2) radical as a major product of C sub(60) fragmentation and less expectedly highlight the existence of a single C atom loss channel. Molecules with more than two carbon atoms are not observed in the post-shock gas. The analysis of the solid component shows that C sub(60) particles are rapidly converted into amorphous carbon with a number of aliphatic bridges. Conclusions. The absence of aromatic CH stretches on the IR spectra indicates that H atoms do not link directly to aromatic cycles. The fast thermal processing of C sub(60) in H sub(2) over the 800-3400 K temperature range leads to amorphous carbon. The analysis hints at a collapse of the cage with the formation of a few aliphatic connections. A low amount of hydrogen is incorporated into the carbon material. This work extends the range of applications of shock tubes to studies of astrophysical interest.